A QUALITATIVE STUDY TO EVALUATE THE PROCESS OF IDENTIFYING PATIENTS AT THE END-OF-LIFE IN PRIMARY CARE. Issue 1 (1st March 2014) - Pocock, LV; Wye, L; Purdy, S
Abstract : Introduction: Identification of patients at the end-of-life is the first step in the care planning pathway and many general practices now have palliative care registers. There is evidence these registers largely comprise of patients with cancer, but little is known about the way in which they are populated. Aim(s) and method(s): To explore GPs' views about the process of identifying patients at the end-of-life and their inclusion on palliative care registers. Methods: A qualitative study with twelve audio-recorded, semi-structured interviews. All interviews were taped and transcribed and data was analysed thematically. The participants were qualified GPs working within practices in three counties in South West England. Results: Most general practices included in the study now have an end-of-life register, although these include mainly cancer patients. Participants discussed the challenges in identifying patients with a non-malignant diagnosis and felt that having end-of-life discussions with these patients was more difficult. Few of the GPs interviewed utilised formal prognostic tools to assist in this identification process. The participants would like more guidance regarding prognosis from secondary care colleagues to facilitate advance care planning. District nurses are central to the process of identifying and managing patients at the end-of-life. Conclusion(s): GPs struggle to prognosticate in non-malignant disease. Cultural change, in the healthcare professions and in the wider public, is necessary before discussion about death and dying from non-malignant disease becomes normal. Further education and training is required, ideally from undergraduate level, to enable doctors to identify patients appropriately and begin these conversations.